2016
DOI: 10.1039/c6an01563h
|View full text |Cite
|
Sign up to set email alerts
|

Development of a functional point-of-need diagnostic for myeloperoxidase detection to identify neutrophilic bronchitis

Abstract: With over 4.8 million Canadians suffering from chronic airway diseases, respiratory exacerbations are currently the leading cause of hospitalization in Canada. In cases of bacterial infection, neutrophil cell density increases from ∼10 million cells per gram to over 15 million cells per gram. As sputum is a direct discharge from the primarily affected areas of respiratory diseases, quantification of granulocytes (including neutrophils) can be used to effectively determine a course of patient treatment. Unfortu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…3 Herein, we describe a rapid LFT for the detection of eosinophil peroxidase (EPX), a biomarker that is eosinophil-specific, and demonstrate its utility for testing of processed patient sputum samples. Our group has recently shown that a rapid, paper-based, lateral flow test (LFT) for myeloperoxidase (MPO) provides a reliable, rapid and potentially cost-effective alternative to cytometry for the identification of neutrophilic bronchitis.…”
Section: Rapid Quantification Of Sputum Eosinophil Peroxidase On a Lamentioning
confidence: 99%
“…3 Herein, we describe a rapid LFT for the detection of eosinophil peroxidase (EPX), a biomarker that is eosinophil-specific, and demonstrate its utility for testing of processed patient sputum samples. Our group has recently shown that a rapid, paper-based, lateral flow test (LFT) for myeloperoxidase (MPO) provides a reliable, rapid and potentially cost-effective alternative to cytometry for the identification of neutrophilic bronchitis.…”
Section: Rapid Quantification Of Sputum Eosinophil Peroxidase On a Lamentioning
confidence: 99%
“…The most widely used and commercially available LFSA is the home pregnancy test, which identifies hormones in urine. This same concept can be applied for recognizing other biomarkers to diagnose a patient with a disease or illness such as the detection of myeloperoxidase as a neutrophilic bronchitis precursor [ 29 ]. These assays work by taking a liquid patient sample (e.g., blood, urine, or saliva) and applying that sample to an absorbent pad on one side of the strip.…”
Section: Disease Detectionmentioning
confidence: 99%
“…Many LFSAs utilize antibodies to detect specific biomolecules [ 29 , 31 , 32 , 33 ]. Before applying the sample to the strip, it must be mixed with detection antibodies that bind to the target molecule that is conjugated to a secondary molecule to provide an analytical output for qualitative analysis.…”
Section: Disease Detectionmentioning
confidence: 99%
See 2 more Smart Citations